VARIASI FORMULA PUMAKKAL TERHADAP KADAR N, P, K PUPUK CAIR LIMBAH AIR KOLAM LELE SEBAGAI BAHAN AJAR BIOLOGI BERUPA LEMBAR KEGIATAN PESERTA DIDIK - Gita Anggraeni; Agus Sutanto; Widya Sartika Sulistiani (EDUBIOLOCK, 2022)
Catfish pond water waste has the potential value to produce fertilizer with innovations in its treatment, converting waste into liquid organic fertilizer (LOF) that can be used by the community as the fertilizer of plants. The aims of this study were 1) To find out which pumakkal formula variation affected the levels of N, P, K in catfish pond wastewater, 2) To find out which pumakkal formula had the best effect on N, P, K levels in catfish pond wastewater, 3) To determine to find out the results of research in the form of LKPD suitable for use as biology teaching materials. This study uses an experimental research design. This study used 1 control and 5 treatments and 3 replications. Treatment 1 used 3 isolates, treatment 2 used 6 isolates, treatment 3 used 9 isolates, treatment 4 used 12 isolates, and treatment 5 used 15 isolates. The results of the test for liquid fertilizer from catfish pond wastewater showed that P5 was the best degrading agent with yields of N (0.533%), P (3.176%), and K (3.994%). Based on the analysis of the validation of teaching materials, this research is suitable for learning biology in the form of student activity sheets with a value of 86% validation of material aspects and 86% of design aspects.